M140 Effect Of Beta-blockade On Lung Function In A Population With Arterial Vascular Disease With And Without Copd. (10th November 2014) - Key, A; West, M; Parry, M; Torella, F; Jack, S; Duffy, N; Walker, PP
Abstract : Introduction: Patients are frequently prescribed β-blockers for heart failure, ischaemic heart disease and peri-operatively, especially for vascular surgery. However, β-blockers remain under prescribed in patients with COPD despite epidemiological evidence indicating little negative impact. This reluctance to use β-blockers is due to concerns about increased airway hyper-responsiveness and bronchoconstriction. As part of a study of peri-operative β-blockade in patients with abdominal aortic aneurysm (AAA) we examined the effect of β-blockers on lung function. Methods: We prospectively recruited 55 AAA patients with no selection bias for COPD or β-blocker use. Thirty eight patients successfully completed detailed lung function testing (PFT) measured by body plethysmography both on and off β-blockers. Subjects already taking β-blockers continued usual treatment while others were prescribed weight adjusted bisoprolol for 48 h. Results: Mean age was 70 (5) years and 33 (77%) subjects were male. 16/38 (42%) were already taking beta-blockers and 5 people (15%) were diagnosed with COPD although 15 (39%) had COPD based on spirometry. Ten (26%) were current smokers and 19 (50%) ex-smokers. The lung function results are shown in the table . Beta-blockade had no significant impact on most lung function measures in both COPD and non-COPD subjects. Specific airways resistance (sRaw) was significantly higher when subjects were taking β-blockers but this effect did not differ between COPD and non-COPD subjects (Δ sRaw: whole group p = 0.004, COPD p = 0.025, non-COPD p = 0.031). Discussion: β-blockers had little effect on static lung function including FEV1 and specific conductance. The small change in resistance was seen in subjects with and without COPD. In this population there appears to be no reason for not using a cardio-selective β-blocker both in this peri-operative setting and for cardiac indications.